Ecdysone inducible gene E75 from black tiger shrimp Penaeus monodon: Characterization and elucidation of its role in molting. Issue 3 (23rd January 2019) - Zhou, Kaimin; Zhou, Falin; Jiang, Song; Huang, Jianhua; Yang, Qibin; Yang, Lishi; Jiang, Shigui
Abstract: Molting is controlled by ecdysteroids, which are synthesized and secreted by the Y‐organ in crustaceans. Ecdysone inducible gene, E75, is an early‐response gene in the 20‐hydroxyecdysone (20E) signaling pathway, with crucial roles in arthropod development. Complementary DNA (cDNA) encoding Penaeus monodon E75 ( PmE75 ) was cloned using RT‐PCR and RACE. PmE75 cDNA was 3526 bp long and encoded a 799‐amino acid protein. Tissue distribution analysis showed that PmE75 was expressed ubiquitously in selected tissues, and was relatively abundant in the epidermis, muscle, and hepatopancreas. Developmental expression revealed that PmE75 was expressed throughout its life cycle. Silencing PmE75 significantly decreased PmE75 expression. Shrimps injected with PBS and dsGFP started molting on Day 7 and had almost completed molting on Day 9, whereas dsPmE75‐ injected shrimp presented no signs of molting. These results suggested that PmE75 might be involved in molting. In situ hybridization results support this hypothesis. To explore the role of 20E and eyestalks in the regulation of molting in P. monodon, exogenous 20E injection and eyestalk ablation (ESA) were performed, and showed that 20E can induce the transcription and expression of PmE75 in the hepatopancreas, epidermis, and muscle, which were signiﬁcantly elevated after ESA. These results provide further insights into our understanding of molting. Abstract : 1. PmE75 was identified and characterized in Penaeus monodon . 2. The expression pattern of PmE75 during the molt cycle was investigated using quantitative real‐time polymerase chain reaction (qRT‐PCR). 3. RNA interference (RNAi) experiment explores the role of PmE75 on molting.